PERCEPTIONS OF PARENTS AND TEACHERS OF THE USE OF MOBILE APPS FOR MATHSEMATICAL EDUCATION - Venter, Marisa; de Wet, Lizette; Swart, James (UNISA: ISTE Conference Mathematics, Science and Technology Education, 2016)
Mobile is full of exciting technologies, and approaches that can help us transform how we teach, work (Stead, 2014). This statement aptly points to the current global trends where many teachers and parents are turning to and experiencing the transformational opportunities that mobile technologies bring to learning (Thiruchelvam, 2014; Grunwald Associates LLC, 2013). Furthermore, mobile educational apps include some of the most useful learning tools that have ever been developed (Prensky, 2012). For example, according to a study commissioned by Encyclopedia Britannica, parents who have downloaded educational apps have observed an improvement in the academic performance of their primary school children as a consequence of using these educational apps on smart-phones and tablets (Daily Mail, 2011). More specifically, educational apps are proving to be particularly useful in maths education. One most recent and comprehensive study involving 800 teachers revealed that 71% of these teachers who use digital educational apps reported improved maths performance amongst their learners (Takeuchi & Vaala, 2014). Despite the opportunities and advantages of mobile educational apps for maths education, the adoption rate in primary schools in the Free State province is extremely low. In order to increase the exposure of teachers and learners to maths educational games, the Information Technology (IT) department at the Central University of Technology (CUT) in SA initiated a project at the start of 2015 where senior post-graduate students were involved in a socio-constructivist project to design and develop appropriate mobile maths applications (apps) for grade 1 to 3 learners in their immediate community. During the first phase of this project each group of post-graduate students were expected to gather data from the parents of the learners and the teacher they collaborated with before they commenced with the second phase of the project which is the design and development of their maths apps. Firstly, they had to determine whether learners have access to mobile devices (in order to pilot the developed apps) and secondly they had to determine what the perceptions of parents and teachers are towards the use of mobile educational maths apps at school and at home which would give an indication of the willingness of parents and teachers to pilot the developed maths apps. The research questions in this study are: 1) To what extent do grade 1 to 3 learners have access to mobile devices? 2) What are the perceptions of teachers and parents towards the use of mobile educational maths apps? 3) Which factors influence the perceptions of parents towards mobile educational maths apps?
Published Conference Proceedings
Keywords: Mathematical education; mobile apps; perceptions; parent perceptions; school learners